Respuesta :

That's a positive slope... I don't know if that's the kind of answer you're looking for, but it's a start I guess.

Since the value of the function is decreasing exponentially as x decreases ,

The function is of the form [tex] y=ae^{bx}+c,b>0 [/tex].

Since the curve passes through (0,6),

[tex] 6=ae^{0}+c,6=a+c [/tex],

Since the curve passes through (-1,0),

[tex] 0=ae^{-b}+c [/tex].

Since [tex] y=-3 [/tex] is a horizontal asymptote,

[tex] -3=ae^{-\infty}+c,c=-3 [/tex]

From the above 3 equations,

[tex] c=-3,a=9,9e^{-b}=3,e^b=3,b=\ln 3 [/tex].

Therefore, the required function is

[tex] y=9e^{\ln 3 x}-3\\
y=9*3^{ x}-3 [/tex].

It can be verified that the curve [tex] y=9*3^{ x}-3 [/tex] passes through [tex] (-2,-2) [/tex].

ACCESS MORE